Pteridophytes of Manambolly Range in Anamalai Tiger Reserve - Johnson, M.; George, Vidyarani; Silvia Juliet, I.; Anwardeen, I.; Ramasubramanian, S.; Ganesan, M. G.; Peter Prem Chakravarthi, J. (Indian Forester, 2026)
The present investigation was undertaken to list the ferns and fern allies of Manambolly Range, Anamalai Tiger Reserve. 87 pteridophytes belonging to 38 genera and 20 families were observed. Among the 20 families observed, Pteridaceae is dominant with 23 species. Pteris (10) and Asplenium (6) = Adiantum (6) > Selaginella (5) > Christella (4) = Athyrium (4) and Bolbitis (3), showed dominance in the studied area. Based on the ecological habitat, a total of 24 species are terrestrial, 16 species are Terrestrial / Lithophytes, 13 species are Terrestrial / Sciophytes, 7 species are epiphyte / Lithophytes, 4 species belong to epiphytes, 3 Riverines, and 4 Rheophytes. Merophyte, epiphytes, lithophytes / Sciophytes and Wetlands pteridophytes also observed. Among the recorded Pteridophytes, 18 Pteridophytes are considered as common, 56 are occasional, 7 are least concern, four listed as endemics, three categorized as risk, one is classified as rare Bolbitis semicordata (Baker) Ching. Of these, Athyrium cumingianum is a new addition to the Pteridophytes of Tamil Nadu. Based on available literature the study revealed various biological activities viz., antibacterial (19), antioxidant (13) and anti-inflammatory (11) of the observed ferns and fern allies of Anamalai Tiger Reserve.